Adverse Childhood Experiences and Academic Procrastination in Emerging Adult Students: The Mediating Effect of Self-Regulation - Tahani, Adhwaa Viera Mahsa; Kurniawati, Kurniawati; Amaranggani, Anindhita Parasdyapawitra; Rahmandani, Amalia (International Journal of Islamic Educational Psychology, 2023)
Academic procrastination has been investigated for its relationship with low self-regulation, which is most likely influenced by adverse childhood experiences (ACEs). This quantitative study utilizes a survey and cross-sectional approach to explore the role of self-regulation in mediating the connection between ACEs and academic procrastination in emerging adult students. A convenience sample of 253 Indonesian students (Mage=20.40; SDage=1.518; Nfemale=97.1%) was obtained. The measurements included the Indonesian version of the Adverse Childhood Experiences Questionnaire (ACE-Q), the short version of the Self-Regulation Questionnaire (SSRQ), and the Academic Procrastination Scale. Statistical analysis was conducted using SPSS version 26. Out of all the participants, 74.3% reported experiencing at least one ACE. Although bivariate correlation analysis revealed a relationship between the variables, hypothesis testing through path analysis indicated that ACE did not have a direct effect on academic procrastination (B=0.871, SE=0.576, β=0.080; p 0.05), except when mediated by self-regulation (Sobel Statistic Test results: Z=4.51; p 0.001). This study highlights the importance of understanding the severity of ACEs in addressing poor self-regulation and mitigating academic procrastination among emerging adult students. Future studies may consider examining different types of ACEs, various aspects of self-regulation, and the role of sex.